Cyclic stability and structure of nanoconfined Ti-doped NaAlH4. (23rd February 2016) - Paskevicius, Mark; Filsø, Uffe; Karimi, Fahim; Puszkiel, Julián; Pranzas, Philipp Klaus; Pistidda, Claudio; Hoell, Armin; Welter, Edmund; Schreyer, Andreas; Klassen, Thomas; Dornheim, Martin; Jensen, Torben R.
Abstract: NaAlH4 was melt infiltrated within a CO2 activated carbon aerogel, which had been preloaded with TiCl3 . Nanoconfinement was verified by Small Angle X-Ray Scattering (SAXS) and the nature of the Ti was investigated with Anomalous SAXS (ASAXS) and X-Ray Absorption Near Edge Structure (XANES) to determine its size and chemical state. The Ti is found to be in a similar state to that found in the bulk Ti-doped NaAlH4 system where it exists as Al1− x Ti x nanoalloys. Crystalline phases exist within the carbon aerogel pores, which are analysed by in-situ Powder X-Ray Diffraction (PXD) during hydrogen cycling. The in-situ data reveals that the hydrogen release from NaAlH4 and its hydrogen uptake occurs through the Na3 AlH6 intermediate when confined at this size scale. The hydrogen capacity from the nanoconfined NaAlH4 is found to initially be much higher in this CO2 activated aerogel compared with previous studies into unactivated aerogels. Graphical abstract: Highlights: High hydrogen capacity is achieved by utilizing activated aerogels. Nanoconfined Ti-based catalysts are in a similar physical/chemical state to bulk. The Ti-based catalyst grows marginally on cycling but remains chemically similar.